Respuesta :

it would be letter d because you switch everything when it says inverse 

Answer:

[tex]f^{-1}=4(x+2)[/tex]

Step-by-step explanation:

[tex]f(x)=\frac{x}{4} -2[/tex]

To find inverse function , replace f(x) with y

[tex]y=\frac{x}{4} -2[/tex]

Swap the variables x and y

[tex]x=\frac{y}{4} -2[/tex], nbw we solve for y

Add 2 on both sides

[tex]x+2=\frac{y}{4}[/tex]

Now to eliminate 4, we multiply 4 on both sides

[tex]y=4(x+2)[/tex]

Replace y with f^-1

[tex]f^{-1}=4(x+2)[/tex]

ACCESS MORE